Edukasi Pemberian Jus Mentimun Untuk Mengurangi Hipertensi dalam Kehamilan: Edukasi Pemberian Jus Mentimun Untuk Mengurangi Hipertensi dalam Kehamilan - ria gustirini (IKesT Muhammadiyah Palembang, 2022)
Hypertension in pregnancy is one of the causes of maternal morbidity and mortality. One of the non-pharmacological treatments that can be given to people with high blood pressure is nutritional treatment. This treatment can be done through eating vegetables that can affect blood pressure, such as cucumber (Cucumis Sativus L.). Cucumber has hypotensive properties (lowers blood pressure). The content in cucumbers can help lower blood pressure, because cucumbers contain potassium (potassium), magnesium, and phosphorus which are effective in treating hypertension. The purpose of this activity is to educate pregnant women about one of the non-pharmacological efforts to reduce high blood pressure that can occur during pregnancy, namely by consuming cucumber juice. The method used is lecture and question and answer. This program is implemented from April to July 2022 with 15 pregnant women as respondents in RT 9 Kel. 13 Ulu, Seberang Ulu District 1 Palembang. The results of community service obtained an average pretest value of 50 points and an average posttest value of 70 points, there was an increase in knowledge of pregnant women about giving cucumber juice to reduce hypertension with an average value of 20 points. With education, it is expected that pregnant women can increase the knowledge of pregnant women about non-pharmacological efforts in reducing high blood pressure that can occur in pregnancy.